2023
DOI: 10.1101/gad.351084.123
|View full text |Cite
|
Sign up to set email alerts
|

ATR inhibition induces synthetic lethality in mismatch repair-deficient cells and augments immunotherapy

Mingchao Wang,
Xiaojuan Ran,
Wendy Leung
et al.

Abstract: The mismatch repair (MMR) deficiency of cancer cells drives mutagenesis and offers a useful biomarker for immunotherapy. However, many MMR-deficient (MMR-d) tumors do not respond to immunotherapy, highlighting the need for alternative approaches to target MMR-d cancer cells. Here, we show that inhibition of the ATR kinase preferentially kills MMR-d cancer cells. Mechanistically, ATR inhibitor (ATRi) imposes synthetic lethality on MMR-d cells by inducing DNA damage in a replication- and MUS81 nuclease-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…We treated WT and ΔSTING B16F10 with 5 μM ATRi for 48 h (Fig 4C; S6B) . ATRi-induced IFN-β was largely STING-dependent, as previously observed (19,31).…”
Section: Resultssupporting
confidence: 85%
“…We treated WT and ΔSTING B16F10 with 5 μM ATRi for 48 h (Fig 4C; S6B) . ATRi-induced IFN-β was largely STING-dependent, as previously observed (19,31).…”
Section: Resultssupporting
confidence: 85%
“…S6F,G ). Although microsatellite instability clearly confers hypersensitivity to ATR inhibition, it is possible that MMR deficiency in of itself could also play a role ( Wang et al 2023 ). While these results support the potential use of ATR inhibitor monotherapy in MSI-H human cancers, the inherent hypersensitivity of MSI-H cells to ATR inhibitors made it difficult to interpret combinatorial effects of dual WRN/ATR inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Another striking example of induced synthetic lethality and antitumor immunity after ATR inhibition has been recently reported regarding Mismatch Repair (MMR) deficient cancer cells [ 112 ]. Also, in tumors with high levels of microsatellite instability (MSI-H) that are characterized by decreased levels of WRN helicase, it has been shown that ATR inhibition may potentiate tumor cell death [ 113 ].…”
Section: The Atr Pathway As a Therapeutic Targetmentioning
confidence: 99%